2008
DOI: 10.1093/jee/101.2.569
|View full text |Cite
|
Sign up to set email alerts
|

Biotypic Diversity in Colorado Russian Wheat Aphid (Hemiptera: Aphididae) Populations

Abstract: The biotypic diversity of the Russian wheat aphid, Diuraphis noxia (Kurdjumov) (Hemiptera: Aphididae), was assessed in five isolates collected in Colorado. Three isolates, RWA 1, RWA 2, and an isolate from Montezuma County, CO, designated RWA 6, were originally collected from cultivated wheat, Triticum aestivum L., and obtained from established colonies at Colorado State University. The fourth isolate, designated RWA 7, was collected from Canada wildrye, Elymus canadensis L., in Baca County, CO. The fifth isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
58
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(62 citation statements)
references
References 0 publications
4
58
0
Order By: Relevance
“…After the appearance of RWA2, Collins et al (2005a) screened 761 germplasm accessions previously determined to be resistant to RWA) and showed that CI2401 also has resistance to RWA2. CI2401 was further shown to be resistant to all eight known biotypes existing in the U.S. (Weiland et al 2008). Qureshi et al (2006) confirmed resistance of CI2401 to RWA2.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…After the appearance of RWA2, Collins et al (2005a) screened 761 germplasm accessions previously determined to be resistant to RWA) and showed that CI2401 also has resistance to RWA2. CI2401 was further shown to be resistant to all eight known biotypes existing in the U.S. (Weiland et al 2008). Qureshi et al (2006) confirmed resistance of CI2401 to RWA2.…”
Section: Introductionmentioning
confidence: 78%
“…RWA2 has since spread to other regions and is now the predominant biotype in the U.S. (Puterka et al 2007). In the following two years, six additional biotypes were discovered in other states within the US Central Great Plains region (Weiland et al 2008). The rapid outbreak of these biotypes within a short period emphasizes the need to identify resistance genes for new biotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Marais et al [32] determined that the Dn7 D. noxia resistance gene from rye was transferred into wheat from the long arm of rye chromosome 1 to form a 1BL/1RS translocation. Dn7 in the cultivar 94M370 provides resistance against all U.S. and South African D. noxia biotypes [33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…The development of new biotypes (populations with the ability to damage normally resistant host plants) endangers the durability of plant resistance (Shufran et al 2000, Burd andPorter 2006), and thus new biotypes clearly limit the usefulness of existing resistant cultivars (Weiland et al 2008). Approximately 50% of the recognized insect biotypes on agricultural crops are aphids (Saxena and Barrion 1987), and it is reported that cereal aphids, such as greenbug, Schizaphis graminum (Rondani) (Burd and Porter 2006), and the Russian wheat aphid, Diuraphis noxia (Kurdjumov) (Weiland et al 2008), have biotypic diversity.…”
mentioning
confidence: 99%
“…Approximately 50% of the recognized insect biotypes on agricultural crops are aphids (Saxena and Barrion 1987), and it is reported that cereal aphids, such as greenbug, Schizaphis graminum (Rondani) (Burd and Porter 2006), and the Russian wheat aphid, Diuraphis noxia (Kurdjumov) (Weiland et al 2008), have biotypic diversity. For example, 22 greenbug biotypes were reported previously Porter 2006, Weng et al 2010).…”
mentioning
confidence: 99%